Mechanical behaviour of graphene oxide embedded epoxy nanocomposite at sub- and above- zero temperature environments. (March 2017) - Prusty, Rajesh Kumar; Rathore, Dinesh Kumar; Sahoo, Sweta; Parida, Varsha; Ray, Bankim Chandra
Abstract: To elucidate the effect of in-service temperature on the stability of interface and hence on the mechanical performance of the graphene oxide filled epoxy (GO-EP) nanocomposite, flexural testing has been performed at various temperatures in the range of −80°C to +90 °C. Mechanically gripped interface at -80°C promotes effective stress transfer resulting in a superior flexural strength of the nanocomposite, which is 82% higher than neat epoxy (EP). Microscopic evidence of the state of the interface as a function of temperature has been presented to evaluate its influence on the overall mechanical performance of the nanocomposite. Highlights: GO-EP nanocomposite exhibits 13% higher strength over EP at 30 °C. The strength enhancement increases to 82% due to interfacial gripping at −80°C. Strength of both GO-EP and EP remains almost same at +90 °C. Failure mode shifts from matrix cracking to interfacial debonding as T rises.